At home parent-administered dressing changes in paediatric burns aftercare: Interviews on parents' experiences of treatment. Issue 2 (March 2022) - Thompson, Dean M.; Thomas, Clare; Hyde, Lisa; Wilson, Yvonne; Moiemen, Naiem; Mathers, Jonathan
Highlights: Parents want to administer dressings for their child's burn injury. Parents often prioritise their child's needs and forgo psychosocial support. Administering dressings functions as an adaptive coping mechanism for parents. Abstract: Objective: Paediatric burn injuries present physical and psychosocial effects for children and their parents, including disruption to family life. Some burns services in the UK enable parents to administer dressing changes at home to reduce the number of hospital visits. To date, there is no research on parents' experiences of administering dressing changes. The aim of this study was to describe parents' experiences of administering dressing changes in paediatric burns aftercare. Methods: Semi-structured research interviews were conducted with a purposive sample of parents recruited from a paediatric burns centre in the UK. The interview addressed the initial offer of at-home dressing changes by clinicians; parental decision-making in relation to dressing changes; training and support received; and the experience of administering dressing changes, including practical and emotional considerations. Thematic analysis of the data was informed by the framework approach, including associative analysis using demographic and clinical characteristics. Results: Seventeen participants were interviewed. Three themes of parents' experiences of administering dressing changes were identified including (1) Parental Identity concerning the newly undertaken responsibility and the impact on the parental role; (2) Challenges, physical or emotional, confronted or lessened by administering dressing changes; and (3) Reassurance provided by healthcare professionals and others to support parents to adopt and maintain parent-administered dressing changes. Conclusion: The qualitative data reported here indicates that parents want to be involved in their child's care by administering dressing changes at home, provided they receive sufficient reassurance that they are able to manage the severity of their child's burn. Parents' concerns about the effectiveness of their dressing changes lacks empirical basis, and this study provides preliminary data to support the development and evaluation of best practice guidance for parent-administered dressing changes in paediatric burns aftercare.